Typifications in the genus Trichocline (Asteraceae: Mutisieae) - Passini, Eduardo (2016)
Concerning the genus Trichocline (Asteraceae: Mutisieae), a neotype is designated for the name Bichenia aurea (≡ T. aurea) and lectotypes are designated for the names Onoseris heterophylla (≡ T. heterophylla), T. humilis and T. linearifolia. Nomenclatural and taxonomic information and IUCN conservation status assessments are given for the four species T. aurea, T. heterophylla, T. humilis and T. linearifolia. In addition, a new record of T. heterophylla for Argentina is reported.